THE ROLE OF ENTREPRENEURS IN THE DEVELOPMENT OF BUSINESS AND MARKETING IN THE DIGITAL ECONOMY - Rakhmonova Feruza Musakulovna (Antis Publisher, 2024)
Business and marketing development in the digital economy requires the use of modern technologies and digital platforms. This process provides opportunities to optimize marketing strategies, establish more effective relationships with customers, and develop the brand globally. Through digital marketing, data analytics, e-commerce, artificial intelligence and innovative technologies, companies will be able to deliver their products and services to customers quickly and efficiently. Also, in the context of the digital economy, social responsibility and environmental approaches also play an important role in increasing customer trust in brands.